Ethical Challenges in Conducting Comparative Adult Education Research: Personal reflections from multi-site research - Kanukisya, Blackson (Papers in Education and Development, 2018)
Ethical issues and the way to address them in the pursuit of research are inevitable. This is true not only in educational research but also issues relating to professionalism and daily life. Different disciplines have different ethical guidelines and laws. However, there are common things that cut across disciplines. Drawing on my experience as a student in a developed country (Norway), and having conducted research in two developing countries (Tanzania and Uganda), in this paper I discuss some ethical challenges that comparative researchers face when conducting research in adult education. The findings of the study suggest that ethical issues and ways to address them are universal. It was also found that ethical issues as regards values are context dependent and they work differently in different contexts. It is concluded that some ethical issues are general and borderless while others are context-dependent. As a consequence special attention should be paid especially to contextual ethical issues. It is recommended that researchers doing research in comparative adult education be aware of the task ahead of them. Equally important, there is a need for researchers to agree on the differences that exist between and among societies and countries which in turn influence the education system. Key words: Comparative and international adult education, dilemma, ethical challenges, research